2009
DOI: 10.1007/s10763-009-9158-y
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Elementary Teachers’ Growth in Knowledge of Models in a Science Capstone Course

Abstract: We used four different methods to determine the best means of assessing over 200 preservice elementary teachers' growth in knowledge of models and their use in K-8 classrooms while participating in the Science Capstone course that focused on the unifying themes of models in science. Each assessment method probed a different aspect of models (from growth in scientific use to need for greater emphasis on the role and use of models) and each used a different method of gathering student responses (Likert-type resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
1
11
0
2
Order By: Relevance
“…During the Capstone course, we introduce students to a variety of model types. In studying their uses and knowledge of models (Everett, Otto & Luera, 2007), we have learned that one common difficulty is the distinction between a model and a process (for example, students often claim that an experiment is a model rather than a process or a target). We have also learned that their knowledge of chemical formulas and balanced chemical equations is uneven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the Capstone course, we introduce students to a variety of model types. In studying their uses and knowledge of models (Everett, Otto & Luera, 2007), we have learned that one common difficulty is the distinction between a model and a process (for example, students often claim that an experiment is a model rather than a process or a target). We have also learned that their knowledge of chemical formulas and balanced chemical equations is uneven.…”
Section: Discussionmentioning
confidence: 99%
“…By pre‐and post‐assessing our students for several semesters, we found that our pre‐service teachers were familiar with physical models but they were less familiar with mathematical models and with mathematical skills such as proportional reasoning (Everett, Otto & Luera, 2007). Proportional reasoning may be introduced in middle school but many college students still experience difficulty in employing such reasoning (Lawton, 1993).…”
mentioning
confidence: 99%
“…The researches indicate that teachers use models in the teaching of any concept, but they have insufficient knowledge about representation and prediction characteristics of the model. The studies that have been made with preservice teachers revealed that their knowledge about models and modelling are insufficient and complicated (Berber & Güzel, 2009;Danusso, Testa & Vicentini, 2010;Everett, Otto & Luera, 2009;Güneş;Bağçı & Gülçiçek, 2004;Justi & Gilbert, 2002;Shen & Confrey, 2007;Smit & Finegold, 1995). On the other hand, researches that have been made with their students are mostly related to the impact on student success and model usage in training (Acher, Arca & Sanmarti, 2007;Çökelez, 2009;Gobert, 2000;Grosslight, Unger, Jay & Smith, 1991;Gümüş, Demir, Koçak, Kaya & Kırıcı, 2008;Maia & Justi, 2009;Marquez et al, 2006;Rotbain, Marbach-Ad & Stavy, 2006;Taylor, Barker & Jones, 2003).…”
Section: Modellingmentioning
confidence: 99%
“…On the other hand, it has been found out that teachers and preservice teachers have deficiencies related models, mathematical models and the nature of mathematical modelling process, namely they have insufficient knowledge about these matters. Hence, a lot of studies in literature indicate that teachers and preservice teachers in different fields have insufficient and complex knowledge about models, modelling, mathematical models and mathematical modelling process (Danusso et al 2010;Everett et al, 2009;Justi & Gilbert, 2003;Smit & Finegold, 1995;Treagust, 2002;Van Driel & Verloop, 1999). For this reason, we may say that it would be beneficial for teachers to have in service seminars and for preservice teachers to have theoretical knowledge in order to remove their insufficiency and to improve their knowledge they have.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
“…La mayoría de ellos centrados en conocer las ideas del profesorado de Primaria y Secundaria en ejercicio y el de Secundaria en formación sobre este tema, siendo casi todos ellos internacionales. Apenas se encuentran trabajos destinados a conocer la visión que presenta el profesorado de Primaria en formación (Everett, Otto y Luera, 2009;Raviolo et al, 2010;Schwarz, 2009). De los identificados, ninguno de ellos ha sido realizado en España, ni presenta una muestra tan amplia de participantes como la de este estudio (201 maestros en formación).…”
Section: Introductionunclassified